Comparison of Lingual and Buccal Orthodontic Therapy on Microbial Parameters and Periodontal Status - Franch, M; Iglesia, F De La; Auladell, A; Walter, A; Clusellas, N; Puigdollers, A (Journal of Medical Biomedical and Applied Sciences, 2019)
AbstractObjective: To compare the periodontal condition and the microbiological status between the vestibular group (VG), lingual group (LG) and control group (CG).Mataerial and Methods: 18 patients(mean age: experimental group: 32 years old; and control group: 25 years old): 6 treated with vestibular fixed appliance, 6 with lingual appliance and 6 subjects in the control groupwho did not receive orthodontic treatment. A periodontal exam was performed before placing braces (T0) and after 4 weeks (T1). The gingival index (GI), plaque index (PI), Bleeding on probing (BOP) and periodontal pocket depth (PPD) was evaluated. Through PCR was detected the presence or absence ofEikenellacorrodens (Ec), Fusobacterium nucleatum (Fn), Agregati bacteractinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), Tannerella forsythensis (Tf), Terponema denticolla (Td), and Prevotella intermedia (Pi).Results: It was found a significant increased in the plaque index and gingival index. No significant changes were found according to BOP and PPD. The microbiological results show significant differences between the control group and the experimental groups in Aa, Tf, Pi, Fn and a tendency to an increase of Pg, Td in both experimental groups. Conclusions: There’s a direct relation between the placement of fixed appliance (vestibular and lingual) and the increase of plaque index and gingival index. Also, the growth of periodonto pathogens in subgingival plaque is promoted. Clinical relevance : This study stresses the importance of monitoring orthodontic patients. Vestibular orthodontic appliance seems to be better than the lingual in terms of less worsening condition during time.